Development of School Principals Strategic Planning in Realizing Performance Productive School - Hidayat, Asep Saepul; Herman, Maman; Sukmara, Ading Rahman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The development of strategic planning in the education system is important in realizing productive school performance, namely schools that have work processes that are consistent with planning elements, achieving optimal work according to its goals. Strategic planning is planning that focuses on achieving the school's vision, mission and goals. In an effort to optimize strategic planning, a management system is needed that is sensitive to needs, changes and challenges, and respects work risks, has a solid, creative, proactive work team, responds to problem solving creatively and innovatively, and has high dedication to achieving goals. This research was carried out using a qualitative approach and exploratory descriptive methods to reveal the required data phenomena, through interview, observation and documentation techniques, which were then analyzed data through phenomenological analysis. Based on the focus of the study in this research, a strategic model of the strategic planning development process was produced which includes 5 components that must be considered in school management, namely: (a) Strategy for achieving vision, mission and goals; (b) Strength of planning consistency; (c) Strengthening team collaboration; (4) Risk Management; and (5) the effectiveness of monitoring and evaluating the achievement of goals and the realization of productive schools.